Navigating Stress And Overload; Systematic Review Based Analysis Of Their Effects On Job Performance In The Healthcare Sector (Journal of Namibian Studies : History Politics Culture, 2022)
Background: Stress and overload are pervasive challenges in the healthcare sector, impacting job performance and patient care quality. Understanding the intricate relationship between these factors is crucial for developing effective interventions to support healthcare professionals.Aim: This study aims to conduct a systematic analysis of the effects of stress and overload on job performance within the healthcare sector, with a focus on identifying key trends, challenges, and potential solutions. Method: A comprehensive literature search was conducted using databases such as PubMed, PsycINFO, Web of Science, and Google Scholar. 15 articles published between 2018 and 2022 were included, focusing on stress, overload, and job performance among healthcare professionals. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed for study selection and data extraction.Results: The systematic analysis revealed several key themes, including the impact of COVID-19 on work stress, coping strategies, work-life balance, organizational support, job satisfaction, work-family dynamics, occupational burnout, and the influence of the workplace environment on performance. Studies highlighted the importance of proactive interventions and organizational support in mitigating stress and improving job performance.Conclusion: The findings underscore the importance of addressing stress and overload in the healthcare sector through targeted interventions and organizational policies. Future research should focus on longitudinal studies and diverse sample recruitment to enhance our understanding of these complex dynamics and inform evidence-based interventions.